Delayed duodenal stump fistula after laparoscopic distal gastrectomy with Billroth-II reconstruction for early gastric cancer: A case report. Issue 27 (8th July 2022) - Kim, Yeo Jin; Kim, Dae Hoon; Choi, Hanlim; Ryu, Dong Hee; Yun, Hyo Yung
Abstract : Duodenal stump fistula (DSF) is one of the most serious complications of gastrectomy. The mean time to diagnosis of DSF is approximately 9 days after operation. Our report describes an extremely rare case of delayed DSF 144 days after a laparoscopic distal gastrectomy. A 58-year-old man with drug-induced liver cirrhosis (Child-Pugh class A) underwent laparoscopic distal gastrectomy with Billroth-II reconstruction for early gastric cancer. On postoperative day 1, he underwent reoperation because of intra-abdominal bleeding. Ongoing bleeding was observed in the stapler line of the duodenal stump and was controlled using metallic surgical clips. The patient was discharged on postoperative day 14, without complications. After 144 days following the first operation, he visited the emergency room with right flank pain and high fever. Computed tomography revealed free air and abscess near the duodenal stump site. Emergency laparotomy, abscess unlooping, and drain insertion were performed. After surgery, bile was drained by intra-abdominal drainage, and fistulography showed a duodenal fistula. The patient was discharged 55 days after his third surgery. This is an extremely rare case of DSF, which may be caused by the metallic surgical clips used for hemostasis of the duodenal stump stapler line. We believe that the use of metallic surgical clips for hemostasis of the duodenal stump after Billroth-II reconstruction should be avoided.